Professional Learning Community Model: A Case Study of a College in Songkhla - Jitnuan, Suwalee; Haruthaithanasan, Theera (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2024)
The aims of this research were: 1. to examine the current state and issues of a Professional Learning Community (PLC), and 2. to develop and validate a PLC model through a case study of a vocational education institution in Songkhla Province. The study employed a qualitative research methodology conducted in two phases: 1. In-depth interviews were used to gather information on real conditions and problems, involving eight key informants selected through purposive sampling, including administrators, teachers, students, and stakeholders. Data were collected using a semi-structured interview protocol with six questions and analyzed through thematic analysis. 2. The PLC model was then validated using expert connoisseurship. The key informants for this phase were 11 experts, including administrators, scholars, and business representatives. Data were collected using expert seminar recordings and assessment forms to verify and confirm the PLC model. The research findings indicated that the PLC model consists of five key elements: 1. A culture of collaboration, which includes strong relationships among current students, alumni, and teachers, professional collaboration among alumni, a friendly atmosphere, and an appropriate SOTUS system; 2. A focus on student-centered learning, incorporating project-based learning, real-world application, competency-based teaching, and student-initiated extracurricular activities; 3. Formative assessment, which involves various evaluation methods aimed at student development, utilizing results from authentic assessments to refine teaching practices, and compiling individualized learner profiles; 4. Collective inquiry, characterized by the exchange of knowledge among teachers in a community of practice, classroom observation, class reflection, and co-teaching; and 5. A commitment to continuous improvement, which emphasizes fostering both internal and external teacher commitment.